Evaluation of change in pterygium induced keratometric astigmatism in patients following pterygium excision with autologous graft surgery - Jain, Amit Kumar; Pandey, Dadan Ji (Nepalese Journal of Ophthalmology, 2020)
Introduction: Pterygium is a common surface disorder of the eye that may cause change in visual acuity of patients by inducing astigmatic refractive error. Surgical excision with grafting is considered the most effective recommended treatment for pterygium. The objective of this study was to evaluate the outcomes of pterygium excision with autologous graft surgery on keratometric astigmatism and visual acuity. Materials and methods: In this study total 64 eyes of 64 patients were enrolled having the diagnosis of pterygium. Prior to the pterygium excision surgery all the enrolled patients were studied for grading of pterygium, clinical symptoms, keratometric values and best corrected visual acuity (BCVA). Postoperatively, BCVA and keratometric readings were recorded at one week, one month, two months and four months intervals. Results: Mean age of study participants was 34.16 ± 8.24 years in the age group of 18-60 years. 42 (65.62%) eyes had grade II pterygium, while 16 (25.0 %) and 6 (9.38%) eyes were having grade III and grade IV pterygium, respectively. Preoperative median and quartiles (25% -75%) horizontal and vertical keratometric values were 43.00 (42.50-44.00) D and 44.25 (43.75-44.50) D, respectively and both reduced significantly to 42.50 (42.50-42.94) D and 42.50 (42.50- 43.00) D, respectively after four months postoperatively. Median keratometric astigmatism before surgery was 1.37 (1.25-1.93) D which reduced significantly to 0.50 (0.32-0.75) D after four months of pterygium excision. Similarly, BCVA improved significantly [0.20(0.16-0.25) vs 0.53 (0.50-0.80)] when assessed postoperatively after four months. Conclusion: Excision of pterygium with autologous graft reduced pterygium-induced keratometric astigmatism and improved BCVA significantly.